2020
DOI: 10.3917/risa.863.0607
|View full text |Cite
|
Sign up to set email alerts
|

La coproduction de valeur publique dans le développement communautaire : les professionnels de terrain peuvent-ils influencer le cours des choses ?

Abstract: Dans cet article, nous analysons les différents rôles joués par les professionnels de terrain lors du processus de création de valeur publique dans le cadre d’un projet de développement communautaire conduit sur le mode de la coproduction. Nous nous intéressons en particulier à la manière dont des professionnels de terrain motivés associent différents rôles – ami, guide, représentant et médiateur – pour autonomiser et inclure les membres du groupe cible et, ce faisant, participer à la création de valeur publiq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Moreover, the shared experience of co-production may leave a more beneficial and enduring legacy compared to traditional service development – often due to service user satisfaction ( Brook et al, 2020 ). Co-production led to interventions that are more likely to meet end-users’ needs through transparency, accountability, learning, responsiveness, and trust, all of which led to a more responsive organization ( Vanleene et al, 2015 ). Although experts raised no limitations regarding the use of co-production of individual interventions, Flinders et al (2016) suggested that factors such as the “rhetoric-reality gap” between the promised and delivered “co-produced” intervention was a significant impedance of successful utilization of co-production ( Flinders et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the shared experience of co-production may leave a more beneficial and enduring legacy compared to traditional service development – often due to service user satisfaction ( Brook et al, 2020 ). Co-production led to interventions that are more likely to meet end-users’ needs through transparency, accountability, learning, responsiveness, and trust, all of which led to a more responsive organization ( Vanleene et al, 2015 ). Although experts raised no limitations regarding the use of co-production of individual interventions, Flinders et al (2016) suggested that factors such as the “rhetoric-reality gap” between the promised and delivered “co-produced” intervention was a significant impedance of successful utilization of co-production ( Flinders et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%